OMISSIONS, ADDITIONS, AND CONFLATIONS IN THE CHESTER BEATTY PAPYRUS - Tarelli, C. C. (The journal of theological studies, 1939)
C. C. TARELLI; OMISSIONS, ADDITIONS, AND CONFLATIONS IN THE CHESTER BEATTY PAPYRUS, The Journal of Theological Studies, Volume os-XL, Issue 4, 1 October 1939, P